The Role of Fermented Milk Containing Probiotic, Dandelion as Prebiotic or their Combination on Serum Metabolites, Enzymes, Testosterone and Testicular Histopathology of Arsenic-Intoxicated Male Rats - Mona A. Al-Damegh,; Moustafa M. Zeitoun,; Ahmed M. Abdel-Salam, (Journal of Basic & Applied Sciences, 2014)
This study aimed at investigating the ameliorative effects of probiotic and/or dandelion aqueous extract to reducing the risk of arsenic (As) intoxication on male rats. Fifty rats were randomly allotted into five groups, group 1(C-) given regular diet and water daily for 56 days, group 2 (C+) given sodium arsenate in drinking water, group 3 (PRO) given sodium arsenate in addition to probiotic, group 4 (PRE) given dandelion aqueous extract plus sodium arsenate (prebiotic) and group 5 (SYN) given sodium arsenate plus probiotic/dandelion extract (synbiotic). At the experiment conclusion rats were sacrificed and blood and testes were collected and taken for analysis and histopathological study, respectively. Glutathione-S-transferase (GST), Alanine aminotransaminase (ALT) and Aspartate aminotransaminase (AST) activities and creatinine, triglycerides (TG) and testosterone(T) concentration were determined and testes histopathology was studied. Creatinine, AST and TG were lower (P<0.01) in PRO, PRE and SYN compared with C+ rats. Arsenic ingestion didn't change rats body weight, but tended to increase testes weight. Also, there found decreases (P<0.05) in testesterone in C+, PRE and SYN-rats, however coadministration of PRO to C+ rats alleviated the toxic effects resulting in a comparable testosterone level to C- rats. Histopathological sections of C+ testes showed dislocation of germinal cells, losing normal architecture, filling seminiferous tubules lumens with cellular debris, slight congestion of blood vessels and thickening of the interstitial tissue. Moreover, in PRE animals, testis showed spermatogenic cells losing their normal architecture with vaculations and increased Leydig cells size. In PRO animals, the testes showed normality of most seminiferous tubules and normal spermatogonia, close to the C- rats. Testes of SYN rats showed little changes in spermatogenic cells structure. In conclusions, the protection of testicular toxicity and liver and kidney functions in arsenic-exposed rats is possible with probiotic or combined coadministration of dandelion-containing probiotic, but not with dandelion extract itself.